The Tower Treasure - Dixon Franklin W.; Franklin W. Dixon (Canada Franklin W. Dixon)
follows Frank and Joe Hardy as they investigate the robbery of Tower Mansion, aiming to clear the name of their friend$1 (Bs father, Henry Robinson.s
Keywords: upright, active, and analytical young masculinity, balancing teenage adventure with moral responsibility and respect for authority; the value of persistence, the importance of integrity, and the power of, and the dangers of hasty, prejudiced judgment